2015
DOI: 10.1021/acs.jpcc.5b05756
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Investigations of the N-Type Semiconducting Polymer P(NDI2OD-T2) and Its Monomer: New Insights in the Reduction Behavior

Abstract: This manuscript provides the first systematic characterization of the electrochemical properties of the high mobility n-type polymer poly{[N,N′-bis(2octyldodecyl)-naphthalene-1,4,5,8-bis (dicarboximide)-2,6-diyl]-alt-5,5′-(2,2′-bithiophene)} (P(NDI2OD-T2)) and its corresponding monomer 2,6-bis(2-bromothien-5-yl)naphthalene-1,4,5,8-tetracarboxylic-N,N′-bis(2-octyldodecyl) diimide (Br-NDI2OD-T2-Br) by cyclic voltammetry and in situ spectroelectrochemistry. Both monomer and polymer reveal a 2-fold reduction to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
87
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(107 citation statements)
references
References 63 publications
17
87
0
Order By: Relevance
“…[101,142] Ludwigs et al performed the in-situ conductance characterization of the high mobility n-type polymer poly{[N,N'-bis(2octyldodecyl)-naphthalene-1,4,5,8-bis (dicarboximide)-2,6-diyl]alt-5,5'-(2,2'-bithiophene)} (P(NDI2OD-T2)). [143] These results showed that the n-doping follows the electron hopping transport according to mixed valence conductivity theory, since a maxima value of conductance is obtained after the negative charging processes, while in the neutral and the fully charged states the material is (almost) nonconductive. Swager et al synthesized soluble di-cationic poly-(pyridinium-phenylenes)s, these polymers, doped with chloride counterions, present ntype conductivity, (a maximal conductivity around 30 Ω À 1 cm À 1 ).…”
Section: N-doping Process and Charge Trappingmentioning
confidence: 85%
See 1 more Smart Citation
“…[101,142] Ludwigs et al performed the in-situ conductance characterization of the high mobility n-type polymer poly{[N,N'-bis(2octyldodecyl)-naphthalene-1,4,5,8-bis (dicarboximide)-2,6-diyl]alt-5,5'-(2,2'-bithiophene)} (P(NDI2OD-T2)). [143] These results showed that the n-doping follows the electron hopping transport according to mixed valence conductivity theory, since a maxima value of conductance is obtained after the negative charging processes, while in the neutral and the fully charged states the material is (almost) nonconductive. Swager et al synthesized soluble di-cationic poly-(pyridinium-phenylenes)s, these polymers, doped with chloride counterions, present ntype conductivity, (a maximal conductivity around 30 Ω À 1 cm À 1 ).…”
Section: N-doping Process and Charge Trappingmentioning
confidence: 85%
“…Ludwigs et al . performed the in‐situ conductance characterization of the high mobility n ‐type polymer poly{[N,N’‐bis(2‐octyldodecyl)‐naphthalene‐1,4,5,8‐bis (dicarboximide)‐2,6‐diyl]‐alt‐5,5’‐(2,2’‐bithiophene)} (P(NDI2OD‐T2)) . These results showed that the n ‐doping follows the electron hopping transport according to mixed valence conductivity theory, since a maxima value of conductance is obtained after the negative charging processes, while in the neutral and the fully charged states the material is (almost) nonconductive.…”
Section: Chemical Aspects Related To In Situ Electrochemical‐conductamentioning
confidence: 96%
“…The changes are similar to those observed upon electrochemical reduction of P(NDI2OD-T2). 47 OTFT characterisation To examine the doping effect of TBAF on the electrical properties of P(NDI2OD-T2), un-doped and doped polymer layers were investigated in OTFT devices with a top-gate, bottom-contact (TG/ BC) configuration fabricated via solution processing. The transfer characteristics of a set of transistors based on un-doped and doped polymer with representative equivalents of dopant are shown in Fig.…”
Section: Uv-vis Absorption Spectroscopymentioning
confidence: 99%
“…To help clarify these questions, we investigate the electron transport, and nanoscale morphology of organic diodes based on solution‐processed P(NDI2OD‐T2) n‐doped with a moderately air‐stable ruthenium organometallic dimer, (RuCp*Mes) 2 (see Figure a, left) . As noted above, P(NDI2OD‐T2) exhibits trap‐free SCLC electron transport, which can be attributed to it high EA of around 4.0 eV .…”
mentioning
confidence: 99%